Green, greener, grey: Disentangling different types of green growth - Marie-Christin Rische; Andreas Marcus Röhlig; Jana Stöver (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2014)
The article proceeds with an introduction into the main definitions of green growth and related concepts and discusses their core defining features. Based thereon, the production framework is introduced and the essential aspects of our definition of green growth are presented. Subsequently, the distinction between green, greener, and grey growth is introduced and their defining features are explained. This is followed by a discussion of the implications from two main issues of the sustainability debate, namely rebound effects and the substitutability of different forms of capital, before we conclude.
Keywords: 330